Programmed death-ligand 1 and tumor-infiltrating lymphocytes (TILs) - low TIL density may predict poorer long-term prognosis in T1 laryngeal cancer - Pakkanen Pihla; Ilmarinen Taru; Halme Elina; Irjala Heikki; Koivunen Petri; Pukkila Matti; Ventelä Sami; Almangush Alhadi; Birkman Eva-Maria; Lindgren Outi; Pohjolainen Virva; Sjöblom Nelli; et al. (SPRINGER, 2025)
We evaluated the prognostic role of programmed death-ligand 1 (PD-L1) and tumor-infiltrating lymphocytes (TILs) in T1 glottic laryngeal squamous cell carcinoma (LSCC). T1 glottic LSCC patients (n = 174) treated at five Finnish university hospitals between 2003 and 2013 were included. Tissue microarray (TMA) blocks were used for PD-L1 immunohistochemistry. TILs were scored from intratumoral and stromal regions in whole tissue sections. Of 174 patients, 92 (53%) had negative, 66 (38%) intermediate, and 16 (9%) high PD-L1 levels. Of 80 patients whose TILs were analyzed, 50 (63%) had low and 30 (38%) high stromal TIL density. Patients with a local recurrence or a new primary tumor of the larynx had lower TIL density than had other patients (p = 0.047). High PD-L1 expression with low stromal TIL density was associated with inferior 5-year disease-specific survival (85% vs. 100%, p = 0.02). In conclusion, in patients treated for T1 glottic LSCC, low stromal TIL density was associated with local recurrences and new primary tumors of the larynx. High PD-L1 expression with low stromal TIL density may be associated with worse survival in T1 glottic LSCC.